2015
DOI: 10.1055/s-0035-1555658
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Educational Intervention Program on the Adoption of Low Back Pain Preventive Behaviors in Nurses: An Application of the Health Belief Model

Abstract: Study Design Randomized controlled trial. Objective The purpose of this study was to identify the effect of a theory-based educational intervention program on the level of knowledge and Health Belief Model (HBM) constructs among nurses in terms of the adoption of preventive behaviors. Methods This pretest/posttest quasi-experimental study was conducted on 100 nurses who were recruited through the multistage sampling method. The nurses were randomly assigned to intervention and control groups. The participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
(23 reference statements)
1
25
0
4
Order By: Relevance
“…Training and lectures effectively increase awareness of safety and self-protection [47] and promote healthy practices among nurses [39]. The WRMD Awareness Month as a cue factor strengthens the belief in safe work behavior through brochure distribution and knowledge and skills competition [27,28]. As part of multidimensional intervention, improving risk perception fully considers the effects of psychological factors on behavior and promotes the adoption of safe working behavior among nurses through changes in attitude and belief.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Training and lectures effectively increase awareness of safety and self-protection [47] and promote healthy practices among nurses [39]. The WRMD Awareness Month as a cue factor strengthens the belief in safe work behavior through brochure distribution and knowledge and skills competition [27,28]. As part of multidimensional intervention, improving risk perception fully considers the effects of psychological factors on behavior and promotes the adoption of safe working behavior among nurses through changes in attitude and belief.…”
Section: Discussionmentioning
confidence: 99%
“…(2) WRMD Awareness Month. The Health Belief Model holds that individual behavior is in uenced by cues that motivate people to change their behavior, such as media reports, advice from others, and reminder brochures [27,28]…”
Section: Improvement Of Risk Perception Of Wrmdmentioning
confidence: 99%
See 1 more Smart Citation
“…In their research, Barrientos‐Trigo et al (2018) summed up the possible interventions for improving nurses’ work environment, such as adequate staffing, making nursing work valued, including nurses in decision‐making processes and good interprofessional communication. Further, Saremi et al (2019) confirmed a negative correlation between knowledge of ergonomics and occupational injuries, which means that training nurses in ergonomics is an effective way of altering occupational behaviour (Sharafkhani, Khorsandi, Shamsi, & Ranjbaran, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sharafkhani és mtsai [5] egy Health Belief Model alapú oktatási programmal mérték fel ápolók tudását a krónikus derékfájdalom prevenciós lehetőségeiről. Négy 60 perces előadást hallgathattak meg az ápolók a derékfájdalom rizikótényezőiről, komplikációiról, a prevenciós tevékenységek előnyeiről, valamint a fájdalommal való megküzdési lehetőségekről.…”
unclassified